2015
DOI: 10.1093/pubmed/fdv138
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity in Africa: a systematic review and meta-analysis

Abstract: BackgroundMaternal obesity is emerging as a public health problem, recently highlighted together with maternal under-nutrition as a ‘double burden’, especially in African countries undergoing social and economic transition. This systematic review was conducted to investigate the current evidence on maternal obesity in Africa.MethodsMEDLINE, EMBASE, Scopus, CINAHL and PsycINFO were searched (up to August 2014) and identified 29 studies. Prevalence, associations with socio-demographic factors, labour, child and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
78
2
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 85 publications
12
78
2
12
Order By: Relevance
“…A recent meta-analysis showed that the prevalence of maternal obesity across Africa ranged from 6.5 to 50.7% [4]. The current study found a high (29.9%) prevalence of obesity among pregnant women (especially women with high parity) in their early pregnancy independent of their residence, education and occupation.…”
Section: Discussionsupporting
confidence: 47%
“…A recent meta-analysis showed that the prevalence of maternal obesity across Africa ranged from 6.5 to 50.7% [4]. The current study found a high (29.9%) prevalence of obesity among pregnant women (especially women with high parity) in their early pregnancy independent of their residence, education and occupation.…”
Section: Discussionsupporting
confidence: 47%
“…Data on overweight/obesity among women of reproductive age in Africa are rare; however, this study found that the prevalence of obesity among of similar age group is comparatively lower in Uganda than other countries in East Africa including Kenya (20.3%) . The lower burden of overweight/obesity should be interpreted with caution as it can confound the magnitude of nutritional problems of the population.…”
Section: Discussionmentioning
confidence: 58%
“…In WHtR; the level of risk is in the order 3 rd ; 2 nd ; 1 st trimester with slight lower percentage value as compared to BMI [16][17][18][19].…”
Section: Insights In Biomedicine Issn 2572-5610mentioning
confidence: 99%